Aplikasi Permainan Edukasi Bahasa Jawa Bagi Siswa SD Berbasis Android - Bayu Surya Atmoko; Isa Bahroni; Dwi Novia Prasetyanti (Journal of Innovation Information Technology and Application (JINITA), 2020)
Technological advances that can be used by the public as a media for education are the development of Android smartphone technology, Android is the most popular of smartphone operating system in Indonesia with a percentage of 92%. Javanese language is one of the regional languages in Indonesia, but now its condition is threatened with extinction due to the smaller number of speakers in daily conversation. SD Negeri Karangmangu 1 is one of the institutions where students experience this problem, because some students feel ashamed and doubtful about using Javanese when talking to older people, due to the lack of Javanese vocabulary they understand. This research about Android Based Application Of Javanese Language Educational Games For Elementary Students. The application built is expected to help and make it easier for students in grades 3-6 to learn Javanese, by packaging Javanese into a fun interactive multimedia application (playing while learning). This application was developed using the Multimedia Development Life Cycle (MDLC) method. The concept of the game is that some Javanese vocabulary will be provided and the user is required to answer and sort the words according to the questions provided before the time runs out, if the answer is correct so the answer and Javanese script will be displayed, as well as the sound of the pronunciation. The results of the application testing were 38% agreed and 62% strongly agreed that the Android Based Application Of Javanese Language Educational Games For Elementary Students can help and make it easier for students in grades 3-6 to learn Javanese language with fun interactive multimedia.